Luminal Bioavailability of Orally Administered ω-3 PUFAs in the Distal Small Intestine, and Associated Changes to the Ileal Microbiome, in Humans with a Temporary Ileostomy. Issue 8 (24th May 2021) - Nana, Gael; Mitra, Suparna; Watson, Henry; Young, Caroline; Wood, Henry M; Perry, Sarah L; Race, Amanda D; Quirke, Philip; Toogood, Giles J; Loadman, Paul M; Hull, Mark A
ABSTRACT: Background: Oral administration of purified omega-3 (ω-3) PUFAs is associated with changes to the fecal microbiome. However, it is not known whether this effect is associated with increased PUFA concentrations in the gut. Objectives: We investigated the luminal bioavailability of oral ω-3 PUFAs (daily dose 1 g EPA and 1g DHA free fatty acid equivalents as triglycerides in soft-gel capsules, twice daily) and changes to the gut microbiome, in the ileum. Methods: Ileostomy fluid (IF) and blood were obtained at baseline, after first capsule dosing (median 2 h), and at a similar time after final dosing on day 28, in 11 individuals (median age 63 y) with a temporary ileostomy. Fatty acids were measured by LC–tandem MS. The ileal microbiome was characterized by 16S rRNA PCR and Illumina sequencing. Results: There was a mean 6.0 ± 9.8-fold and 6.6 ± 9.6-fold increase in ileal EPA and DHA concentrations (primary outcome), respectively, at 28 d, which was associated with increased RBC ω-3 PUFA content ( P ≤ 0.05). The first oral dose did not increase the ileal ω-3 PUFA concentration except in 4 individuals, who displayed high luminal EPA and DHA concentrations, which reduced to concentrations similar to the overall study population at day 28, suggesting physiological adaptation. Bacteroides, Clostridium, and Streptococcus were abundant bacterial genera in the ileum. Ileal microbiome variability over time and between individuals was large, with no consistent change associated with acute ω-3 PUFA dosing. However, high concentrations of EPA and DHA in IF on day 28 were associated with higher abundance of Bacteroides ( r 2 > 0.86, P < 0.05) and reduced abundance of other genera, including Actinomyces ( r 2 > 0.94, P < 0.05). Conclusions: Oral administration of ω-3 PUFAs leads to increased luminal ω-3 PUFA concentrations and changes to the microbiome, in the ileum of individuals with a temporary ileostomy. This study is registered on the ISRCTN registry as ISRCTN14530452.